Are Alpha-2D Adrenoceptor Subtypes Involved in Rat Mydriasis Evoked by New Imidazoline Derivatives: Marsanidine and 7-Methylmarsanidine? - Joanna Raczak-Gutknecht; Teresa Frąckowiak; Antoni Nasal; Anita Kornicka; Franciszek Sączewski; Roman Kaliszan (SAGE Publishing, 2017)
The imidazoline compounds may produce mydriasis after systemic administration to some species (rats, cats, and mice). In mydriatic activity of imidazolines, α 2D -adrenoceptors subtype(s) seems to be involved. In this study, the pupil dilatory effect evoked by 2 newly synthesized imidazoline derivatives-α 2 -adrenoceptor agonists: marsanidine and 7-methylmarsanidine-was compared. The compounds were tested alone as well as in the presence of α 2 -adrenoceptor antagonists (nonselective, yohimbine, and selective toward the following α 2 -adrenoceptor subtypes-α 2A -2-[(4,5-dihydro-1H-imidazol-2-yl)methyl]-2,3-dihydro-1-methyl-1H-isoindole maleate (BRL44408), α 2B -2-[2-(4-(2-methoxyphenyl)piperazin-1-yl)ethyl]-4,4-dimethyl-1,3-(2H,4H)-isoquinolindione dihydrochloride (ARC239), α 2C -JP1302, α 2D -2-(2,3-dihydro-2-methoxy-1,4-benzodioxin-2-yl)-4,5-dihydro-1H-imidazole hydrochloride [RX821002]). The agonists were studied in male Wistar rats and were administered intravenously in cumulative doses. The antagonistic compounds were given in a single dose before the experiment with marsanidine or 7-methylmarsanidine. Pupil diameter was measured with stereoscopic microscope equipped in green light filter. Marsanidine and 7-methylmarsanidine exerted marked mydriatic effects. BRL44408, JP1302, and ARC239 did not cause significant parallel shift to the right of the dose-effect curves obtained for both imidazolines. In case of yohimbine and RX821002, the marked parallel shifts of dose-response curves were observed, with the antagonistic effects of RX821002 more pronounced. In vivo pharmacodynamics experiment suggests that α 2D -adrenoceptor subtype is mainly engaged in mydriatic effects evoked in rats by imidazoline derivatives, in particular by clonidine.